Research trends and hotspots on the links between caveolin and cancer: bibliometric and visual analysis from 2003 to 2022 - Tan, Yaqian; Song, Qi (Frontiers in pharmacology, 2023)
Introduction: Extensive studies indicated that caveolin is a key regulator in multiple cellular processes. Recently, growing evidence demonstrated that caveolin is critically involved in tumor progression. Since no relevant bibliometric study has been published, we performed a bibliometric and visual analysis to depict the knowledge framework of research related to the involvement of caveolin in cancer. Methods: Relevant studies published in English during 2003–2022 were obtained from the Web of Science Core Collection database. Three programs (VOSviewer, CiteSpace, and R- bibliometrix ) and the website of bibliometrics ( http://bibliometric.com/ ) were applied to construct networks based on the analysis of countries, institutions, authors, journals, references, and keywords. Results: A total of 2,463 documents were extracted and identified. The United States had the greatest number of publications and total citations, and Thomas Jefferson University was the most productive institution. Michael P. Lisanti was the most influential scholar in this research domain. Cell Cycle was the journal with the most publications on this subject. The most local-cited document was the article titled “Caveolin-1 in oncogenic transformation, cancer, and metastasis.” A comprehensive analysis has been conducted based on keywords and cited references. Initially, the research frontiers were predominantly “signal transduction”, “human breast cancer,” “oncogenically transformed cells,” “tumor suppressor gene,” and “fibroblasts.” While in recent years, the research emphasis has shifted to “tumor microenvironment,” “epithelial mesenchymal transition,” “nanoparticles,” and “stem cells.” Conclusion: Taken together, our bibliometric analysis shows that caveolin continues to be of interest in cancer research. The hotspots and research frontiers have evolved from the regulation of cancer signaling, to potential targets of cancer therapy and novel techniques. These results can provide a data-based reference for the guidance of future research.